Black working-class students’negotiation of boundaries across time and space: Alongitudinal analysis - Bangeni, Bongi; Kapp, Rochelle (Critical Studies in Teaching and Learning, 2023)
This article critiques representations of black South African students as victims, as colonised by academic discourse or as entitled millennials in the current debates about decolonisation in higher education. It argues that, albeit from different ideological perspectives, such representations depict black students’ experiences as homogenised and reified, and separate identity from the processes of learning. We draw on data from two qualitative longitudinal studies to analyse the ways in which black working-class students are positioned by the expected subject positions within the academy and at home. We illustrate the diverse and contradictory ways in which the participants reposition themselves as they straddle the boundaries of home and the academy over time. The article argues that the activity of straddling boundaries and making meaning from a diversity of positions is situated agentic work, and is central to learning, to critical engagement, and to enabling new ways of knowing and being.